PELAKSANAAN TUGAS GURU PROFESIONAL DI SEKOLAH MENENGAH ATAS NEGERI KOTA PARIAMAN - Pipit Afriyani. D (Universitas Negeri Padang, 2013)
The background of this research from the author's observation Implementation Task Teachers in high schools Pariaman still lacking. The purpose of this study is to find out about the execution of tasks in the Senior High School Teachers Pariaman Duty seen from the aspect of Teaching, Professional Development, Professional Support. The population in this study all professional teachers High School in the city of Pariaman, amounting to 183 people, while the sample size is determined by the table Krejci and earned by 56 people. Sampling technique using cluster sampling techniques. The results Implementation Task Teachers in high schools Pariaman.in general, implementation of teacher professional duties in carrying out duties at the high category with a score of 4.2. Key word; assignment of teachers